2016
DOI: 10.1242/jcs.194738
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in actin dynamics reconfigure protein complexes that modulate GCN2 activity and promote an eIF2 response

Abstract: Genetic and pharmacological interventions in yeast and mammalian cells have suggested a cross-talk between the actin cytoskeleton and protein synthesis. Regulation of the activity of the translation initiation factor 2 (eIF2) is a paramount mechanism for cells to rapidly adjust the rate of protein synthesis and to trigger reprogramming of gene expression in response to internal and external cues. Here, we show that disruption of F-actin in mammalian cells inhibits translation in a GCN2-dependent manner, correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 54 publications
2
39
0
Order By: Relevance
“…Diverse cellular stresses, including nutrient depletion, DNA damage, and oxidative stress among others, inhibit TOR and shift cellular programming away from growth. These stressors activate the integrated stress response, a highly integrated cellular program that activates autophagy (Kroemer, Marino, & Levine, 2010), promotes chaperone activity (Starck et al, 2016), and inhibits growth‐associated protein translation in favor of highly selective translation of stress response proteins such as ATF4 (Silva, Sattlegger, & Castilho, 2016). EEF1A and TOR signaling intersect at the level of the GCN2 kinase (Silva et al, 2016; Wengrod et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Diverse cellular stresses, including nutrient depletion, DNA damage, and oxidative stress among others, inhibit TOR and shift cellular programming away from growth. These stressors activate the integrated stress response, a highly integrated cellular program that activates autophagy (Kroemer, Marino, & Levine, 2010), promotes chaperone activity (Starck et al, 2016), and inhibits growth‐associated protein translation in favor of highly selective translation of stress response proteins such as ATF4 (Silva, Sattlegger, & Castilho, 2016). EEF1A and TOR signaling intersect at the level of the GCN2 kinase (Silva et al, 2016; Wengrod et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…An interplay of actin dynamics and gene expression has already been proposed in mammalian cells. For instance, it was found that the treatment of primary murine cells with chemical agents provoking F‐actin disruption ellicited a global inhibition of translation and protein synthesis and that this activated the cellular stress response (Silva, Sattlegger, & Castilho, 2016). Here, we show that a decrease of actin polymerization, either spontaneous or elicited by ACTC1 overexpression, rather mediated an increase of recombinant protein expression by CHO cells and that this did not impair cell division or viability.…”
Section: Resultsmentioning
confidence: 99%
“…Cryo-EM studies have highlighted the close interaction between the actin cytoskeleton and components of the protein translational machinery, including, but not limited to, ribosomes [51]. Indeed, mRNA transcripts, polysomes, eukaryotic initiation and elongation factors and aminoacyl-tRNA synthetases have all been shown to associate with the cytoskeleton [52]. This proximity is functionally important because efficient protein translation depends on an intact cytoskeleton, and deletion of cytoskeleton-regulating proteins can affect the initiation of protein translation [53,54].…”
Section: Cell Mechanics and The Protein Translation Machinerymentioning
confidence: 99%
“…In mammalian cells, depolymerization of actin filaments leads to a major reduction in resumption of protein translation in response to cold shock [53], whereas in yeast an intact actin filament network is a pre-requisite for regulation of protein synthesis [54]. More recently, it was demonstrated that disruption of filamentous actin in mammalian cells impedes translation via phosphorylation of the α-subunit of eukaryotic initiation factor eIF2, the heterotrimeric factor that delivers the initiator methionyl-tRNA Met to the ribosome [52]. A wide range of stressors, including amino acid starvation, leads to phosphorylation of eIF2α on Ser51 and downstream inhibition of general protein synthesis [75].…”
Section: Cell Mechanics and The Protein Translation Machinerymentioning
confidence: 99%
See 1 more Smart Citation